Treatment with Ruta graveolens 5CH and Rhus toxicodendron 9CH may reduce joint pain and stiffness linked to aromatase inhibitors in women with early breast cancer: results of a pilot observational study. Issue 4 (November 2016) - Karp, Jean-Claude; Sanchez, Carole; Guilbert, Philippe; Mina, William; Demonceaux, Antoine; Curé, Hervé
Abstract : Objective: To determine the possible effect of two homeopathic medicines, Ruta graveolens 5CH and Rhus toxicodendron 9CH, in the prevention of aromatase inhibitor (AI) associated joint pain and/or stiffness in women with early, hormone-receptor positive, breast cancer. Methods: This prospective, unrandomized observational study was carried out between April and October 2014. Women were recruited in two groups, according to which of the two study centres they attended: one receiving homeopathy in addition to standard treatment (group H) and a control group, receiving standard treatment (group C). All women were treated with an AI. In addition, women in group H also took Ruta graveolens 5CH and Rhus toxicodendron 9CH (5 granules, twice a day) up to 7 days before starting AI treatment. The homeopathic medicines were continued for 3 months. Demographic and clinical data were recorded using a self-assessment questionnaire at inclusion (T0) and 3 months (T3). Primary evaluation criteria were the evolution of scores for joint pain and stiffness, the impact of pain on sleep and analgesic consumption in the two groups after 3 months of treatment. Results: Forty patients (mean age 64.9 ± 8.1 years) were recruited, 20 in each group. Two-thirds of the patients had joint pain before starting AI treatment. There was a significant difference in the evolution of mean composite pain score between T0 and T3 in the two groups (−1.3 in group H vs. +3.4 in group C; p = 0.0001). The individual components of the pain score (frequency, intensity and number of sites of pain) also decreased significantly in group H. Nine patients in group C (45%) vs. 1 (5%) in group H increased their analgesic consumption between T0 and T3 (p = 0.0076). After 3 months of treatment, joint pain had a worse impact on sleep in patients in group C (35% vs. 0% of patients; p = 0.0083). The differences observed in the evolution of morning and daytime stiffness between the two groups were smaller (p = 0.053 and p = 0.33, respectively), with the exception of time necessary for the disappearance of morning stiffness which was greater in group C (37.7 ± 23.0 vs. 17.9 ± 20.1 min; p = 0.0173). Conclusion: These preliminary results suggest that treatment with Ruta graveolens 5CH and Rhus toxicodendron 9CH may decrease joint pain/stiffness in breast cancer patients treated with AIs. A larger-scale randomized study is required to confirm these results. Highlights: Homeopathic treatment may have a favourable impact on joint pain and stiffness. Homeopathic treatment may decrease analgesic consumption for joint pain. Pain may have less impact on sleep in patients given homeopathic treatment.